2008
DOI: 10.1113/jphysiol.2007.147967
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of prenatal nutrient restriction on cardiovascular and hypothalamic‐pituitary‐adrenal function

Abstract: The perinatal environment is a powerful determinant of risk for developing disease in later life. Here, we have shown that maternal undernutrition causes dramatic changes in heart structure and hypothalamo-pituitary-adrenal (HPA) function across two generations. Pregnant guinea pigs were fed 70% of normal intake from gestational days 1-35 (early restriction; ER), or 36-70 (late restriction; LR). Female offspring (F 1 ) were mated and fed ad libitum to create second generation (F 2 ) offspring. Heart morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
82
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 53 publications
0
82
1
Order By: Relevance
“…Female rats born small-for-gestational age (SGA) were more likely to have SGA infants than mothers that were not born SGA (Klebanoff et al, 1997). In guinea pigs, both the F1 and F2 generations of undernourished F0 mothers showed increased thickness of septal and left ventricular walls of the heart (Bertram et al, 2008). In addition, both F1 and F2 animals had increased basal cortisol and altered HPA stress reactivity.…”
Section: Transgenerational Effectsmentioning
confidence: 98%
“…Female rats born small-for-gestational age (SGA) were more likely to have SGA infants than mothers that were not born SGA (Klebanoff et al, 1997). In guinea pigs, both the F1 and F2 generations of undernourished F0 mothers showed increased thickness of septal and left ventricular walls of the heart (Bertram et al, 2008). In addition, both F1 and F2 animals had increased basal cortisol and altered HPA stress reactivity.…”
Section: Transgenerational Effectsmentioning
confidence: 98%
“…For example, stress during pregnancy results in increased activity in the F2 generation (Wehmer et al, 1970). Maternal malnutrition and synthetic glucocorticoid administration alter HPA axis functions in both the F1 and F2 generations, that can lead to stress-related behavioral phenotypes (Kostaki et al, 2005;Bertram et al, 2008). In some models, stress exposure of the female results in transmission to the F2 generation, but only through F1 males (Morgan and Bale, 2011;Saavedra-Rodriguez and Feig, 2012), suggesting male gamete-mediated F1 to F2 transmission.…”
Section: Effect Of Stress Abused Drugs and Toxins Across Generationsmentioning
confidence: 99%
“…These stimuli are likely to be mediated via a number of different hormones and immune factors, but glucocorticoids have been singled out as one of the most prevalent factors. Epidemiological and experimental animal studies have revealed that excess glucocorticoids in utero can be linked to the development of diseases such as hypertension [36][37][38][39][40][41][42], depression [43], cardiovascular disease [44], diabetes [45][46] and attention deficit disorders [23,47]. Further, the outcomes or the severity of these diseases are worse if the offspring affected are male [37][38][39][48][49][50][51].…”
Section: Excess Glucocorticoids and The Programming Of Diseasementioning
confidence: 99%